Genotype analysis and identification of novel mutations in a multicentre cohort of patients with hereditary factor X deficiency. Issue 1 (January 2019) - Mitchell, Michael; Gattens, Michael; Kavakli, Kaan; Liesner, Ri; Payne, Jeanette; Norton, Miranda; Austin, Steven
Abstract : N/A: The objective was to examine the genotypic and phenotypic characteristics of individuals with hereditary factor X deficiency (FXD), a rare autosomal recessive bleeding disorder caused by mutations in the F10 gene located on chromosome 13q34-ter. To date, 149 F10 mutations have been identified as contributory to FXD. Three open-label phase 3 trials enrolled individuals with mild, moderate, or severe FXD. Individuals received plasma-derived factor X concentrate as routine prophylaxis, to treat bleeds, and/or during or after surgery. F10 genotyping was performed (studies 1 and 2) or genotype data was collected at screening (study 3), and identified F10 mutations were compared against the Human Gene Mutation Database to assess novelty. Genotype data were combined to evaluate the number, type, and novelty of the F10 mutations identified. Genotype data were available for 24 of 27 individuals with mild ( n = 2), moderate ( n = 2), or severe ( n = 20) FXD. Analyses identified 22 separate mutations, including 15 missense mutations, 2 deletions, 4 splice site mutations, and 1 nonsense mutation. Sixteen individuals had homozygous mutations; 8 had compound heterozygous mutations. Eleven unique novel mutations (all compound heterozygous) were identified in seven individuals: six missense mutations, three splice site mutations, one exon deletion, and one nonsense mutation. In silico analyses strongly supported the pathogenicity of all novel mutations. The identification of 11 novel F10 mutations provides a substantial contribution to the mutations known to cause FXD.